(t, n) threshold secret sharing scheme without SDC - ZHOU Fu-cai; LIN Long; WANG Jin-ying; XU Jian (Tongxin xuebao)
By means of the intractability of ellipse curve discrete logarithm problem（ECDLP）,a（t,n） secret sharing threshold scheme based on ellipse curve cryptography was proposed.Generally speaking,there are two kinds of threshold schemes: a threshold scheme with share distribution center（SDC） and a threshold scheme without SDC.Under distrib-uted situation,there is no such a center can be completely trusted by all members of the group,a threshold scheme with-out SDC appears more attractive.In the scheme without SDC all of the members generate the group public key and pri-vate keys.When new numbers join the group secret sharing should be updated by period.An example of the scheme us-ing the small number was given.The security of the scheme was analyzed in the final.